Enhancing Skill Performing Competency among Handball Players: Comparative Effects of Mental Imagery, Self-Talk, and Their Combination - Upadhyay, Kautilya; Phulkar, Ashish; Yadav, Satpal; Sharma, Arnav; Terang, Varun (Physical Education Theory and Methodology, 2025)
Objectives. The objective of this study was to examine the comparative and combined effects of mental imagery and self-talk training on handball players’ jump-shoot skill performing competency. The study aimed to determine whether integrating both psychological techniques leads to greater improvement in motor performance than using either strategy alone or traditional practice. Materials and Methods. Forty male handball players were randomly assigned to four groups (n = 10 each): Mental Imagery and Self-Talk, Mental Imagery, Self-Talk, and Control. The experimental groups received a six-week psychological skills training intervention, while the control group participated only in regular handball practice. The Handball Jump-Shoot Skill Performing Competency test was administered before and after the intervention. Data were analyzed using Analysis of Covariance (ANCOVA) to control for pre-test differences, followed by Bonferroni post-hoc tests for pairwise comparisons. Results. The ANCOVA revealed a significant group effect on post-test scores, F(3, 35) = 18.18, p < .001, with an adjusted R² = .665. The Mental Imagery and Self-Talk group demonstrated the highest improvement (pre-mean = 13.90; post-mean = 17.70), followed by the Mental Imagery and Self-Talk groups, while the Control group showed minimal gain. Post-hoc analysis confirmed that the combined intervention produced significantly better results than all other groups (p < .05). Conclusions. The findings suggest that the combined application of mental imagery and self-talk was the most effective psychological intervention for enhancing handball jump-shoot skill performance, emphasizing the synergistic value of integrating cognitive and motivational training strategies in sport performance improvement.